New Technological Knowledge of the Rotary Turning Tool - Vasilko, Karol; Pilc, Jozef (Manufacturing Technology Journal, 2013)
In the previous paper [12], a design of location and construction of a rotating turning tool has been documented. Sporadically, this tool has appeared in literature [1], [2], [3], [4] in different applications. So far its operational characteristics, mainly its considerable influence on machined surface quality, exceptional durability and possibility to be used to turn hard machinable materials have not been appreciated. Some of its priorities are verified in the paper.
Keywords: rotating tool; tool durability; machined surface quality